PENGARUH TAX PLANNING DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR PADA BEI PERIODE 2019 – 2023 - Mahda, Muzma Zalma; Sugeng, Andry (Publika Citra Media, 2025)
This research aims to examine and provide evidence regarding the influence of tax planning and dividend policy on firm value. The study was conducted on energy sector companies listed on the Bursa Efek Indonesia during the 2019-2023 period. The data used in this research is secondary data. The sampling method employed was purposive sampling based on predetermined criteria, resulting in a sample of 12 companies with 5 years of observation from a total population of 87 companies. The panel data regression method was used as the research methodology. Hypothesis testing was conducted using E-views Version 12. The results of this research indicate that, simultaneously, tax planning and dividend policy affect firm value. Tax planning has no effect on firm value, while dividend policy has an effect on firm value.